Mind mapping as a new method that supports readiness forprimary school - POLAT, ÖZGÜL (My University, 2021)
In the changing and developing world, the methods and approaches which promote learning experiences of individuals develop at the same pace. If such methods are integrated into the education system as an alternative to traditional teaching methods, it will enrich the learning experience for children and provide teachers with an opportunity to reach more children. As part of this, the research aims to use the mind mapping method to develop school readiness skills of preschoolers. This study was designed with a quantitative research procedure and was planned using a quasi-experimental design. The working group for the study was made up of 44 children, of which, 21 belong to the experimental group and 23 the control group. For the first step of the study, teachers were given mind mapping training and later the children in the experimental group were subjected to mind mapping applications in 22 themes (school, numbers, shapes, our healty, cooperation, emotions, nature…), comprising 7 large group and 15 individual mind mapping applications. The mind map theme of the week was covered every day in that week's program. As a result of the study, a significant difference in scores for school readiness skills between the experimental and control groups was revealed for all sub-dimensions in favour of the experimental group. The study indicates that the mind mapping technique applied with the children in the experimental group supports their readiness for primary school considerably.
Keywords: early childhood education; mind mapping; preschool education; school readiness.